(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
This article addresses the issue of household consumption expenditures from the perspective of young consumers. The main goal of the research was to identify household consumption expenditures from the viewpoint of young consumers, specifically focusing on expenditures on food. The study involved 384 households. The primary objective was achieved through the use of primary data collected via a questionnaire. The conducted research demonstrated that the expenditures and behaviors of young consumer households are changing. The gathered research results show us how incomes, expenditures and consumption behaviors of young consumers are shaped.